Pesticide application equipment for use in agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Pesticide application equipment for use in agriculture - Vol. 1 Manually carried equipment FAO Agricultural Services Bulletin 112/1 by G Matthews and E Thornhill 1994 163pp ISBN 92 5 103582 2